Examination of new import substitution in the sector of agro-industry (Revista de Investigaciones Universidad del Quindío, 2022)
The expansion of globalization procedures, the intensified competition, and the prolonged technological and economic sanctions against Russia necessitate adapting the strategic aims regarding import substitution. The current study intends to analyze a new substitution for import in the agro-industrial complex as a fundamental element in surmounting interregional differentiation. To that end, general scientific and particular approaches of cognition are utilized, including the principles of dialectics, synthesis and analysis, generalization and comparison, typologies and groupings, and empirical techniques. The examination of the morphogenesis of the procedure under investigation facilitates establishing that the building’s features and execution of the import substitution policy under the circumstances of an innovation-oriented economy haven’t been thoroughly analyzed yet; the particular benefits and poor connections of import substitution measures haven’t been fully recognized. There stands no mere explanation of the chief classifications; the limitations and possibilities of implementing import substitution policy concerning the necessity for increasing the level of innovative activity haven’t been completely justified. All of these needs the prompt growth of methodological and theoretical methods regarding the tools and strategy for import substitution.
Keywords: agriculture; economic sanctions; economic crisis; technological sanctions